Experimental Studies of Static Mixers and Twin Screw Extruders - Jaffer, Shaffiq A. (My University, 1998)
The laminar flow field in a Kenics KM® static mixer and a Werner and Pfleiderer ZSK-30® twin screw extruder (TSE) has been studied using laser induced fluorescence (LIF) coupled with digital image analysis, particle image velocimetry (PIV) and laser Doppler anemometry (LDA). The objective of this study was to observe the flow fields in these two devices, to determine their mixing capabilities qualitatively and quantitatively. Mixing in the static mixer was quantified by measurement of the number average striation thickness, variance of striation widths and interfacial area for elements with 90 degrees of twist. From flow visualisation and LDA measurements, transitions were observed in the flow where vortices developed above the first and second elements. These vortices did not appreciably enhance mixing after 4 to 5 elements with an aspect ratio (L/D) of 1.0. The velocity field measured over the first four elements (L/D = 1.5), captured the mixing nature of the static mixer, where flow was split at the leading edge and recombined at the trailing edge of the elements. Recirculations in the radial plane were observed where fluid flowed from the high-pressure side of the element forward out along the tube wall to the low-pressure side or suction side. The radial flow field required a development length to allow the flow to build in magnitude. The rate of deformation analysis on the flow field indicated that mixing efficiency would be increased if the first element had a larger helix angle. The highest rates of deformation were measured at the junctions between elements, and between the element and tube surfaces. The visualisations coupled with image analysis for the TSE demonstrated clearly that the mixing was enhanced by placing a reverse conveying element directly after the last set of kneading discs in the mixing section. The velocity results for the screw profile with extended first and last discs (geometry A) showed an increase in back flow and recirculations with increasing screw rotation. When a forward conveying element was used before and after the kneading discs (geometry B), higher radial and lower axial velocities were measured. The fluid in the direction of rotation and no back-mixing or recirculations in the flow were measured. Results of a 3D model for the simulation of flow in the kneading disc region and the PIV measurements were compared. Results for geometry A are in good qualitative agreement for low flow rates. Geometry B showed better agreement at higher flow rates compared to lower flow rates. The performance of the kneading discs were characterized based on the shear, elongation and the magnitude of the rate of deformation tensor within the measured flow fields. For the various cases of screw rotation speed, the largest rates of deformations (elongation and shear) were seen at the first and last disc of the kneading block where transitions occurred.
Keywords: Chemical Engineering; Chemical Engineering